Variable Neighborhood Search 9th International Conference, ICVNS 2022, Abu Dhabi, United Arab Emirates, October 25-28, 2022, Revised Selected Papers - Sleptchenko, Andrei; Sifaleras, Angelo; Hansen, Pierre (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This volume constitutes the proceedings of the 9th International Conference on Variable Neighborhood Search, ICVNS 2023, held in Abu Dhabi, United Arab Emirates, in October 2022. The 11 full papers presented in this volume were carefully reviewed and selected from 29 submissions. The papers describe recent advances in methods and applications of variable neighborhood search.
A metaheuristic approach for solving Monitor Placement Problem -- A VNS-based heuristic for the minimum number of resources under a perfect schedule -- BVNS for Overlapping Community Detection -- A Simulation-Based Variable Neighborhood Search Approach for Optimizing Cross-Training Policies -- Multi-Objective Variable Neighborhood Search for improving software modularity -- An Effective VNS for Delivery Districting -- BVNS for the Minimum Sitting Arrangement problem in a cycle -- Assigning Multi-Skill Confgurations to Multiple Servers with a Reduced VNS -- Multi-Round Infuence Maximization: A Variable Neighborhood Search Approach -- A VNS based heuristic for a 2D Open Dimension Problem -- BVNS for the bi-objective multi row equal facility layout problem.
Keywords: Computer science -- Mathematics; Discrete mathematics; Algorithms; Mathematics of Computing; Discrete Mathematics in Computer Science; Design and Analysis of Algorithms